2016
DOI: 10.6028/nist.tn.1914
|View full text |Cite
|
Sign up to set email alerts
|

2015 Location-Based Services R [and] D Summit Report

Abstract: to build on the findings presented in the 2015 Location-Based Services R&D Roadmap Report. The Location-Based Services (LBS) Summit-held October 21-22, 2015-intended to socialize the roadmap with a broader stakeholder base and determine the core technology challenges inhibiting public safety's effective and expanded use of LBS in daily operations. The Summit identified clearly defined LBS technology gaps, prioritized capabilities, and specific problem statements that could be addressed using NIST R&D funds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…It was observed that genistein decreased cholesterol concentrations in GPR30 −/− mice, even though GPR30 activation has been reported to be associated with an increase in LDL receptor expression and, consequently, a decrease in plasma cholesterol. [46,47] However, as we have already reported there is evidence that genistein present in soy protein stimulates the expression of fibroblast growth factor 15, [48] which promotes a decrease in serum cholesterol concentrations, which could be occurring in our study.…”
Section: Discussionsupporting
confidence: 44%
“…It was observed that genistein decreased cholesterol concentrations in GPR30 −/− mice, even though GPR30 activation has been reported to be associated with an increase in LDL receptor expression and, consequently, a decrease in plasma cholesterol. [46,47] However, as we have already reported there is evidence that genistein present in soy protein stimulates the expression of fibroblast growth factor 15, [48] which promotes a decrease in serum cholesterol concentrations, which could be occurring in our study.…”
Section: Discussionsupporting
confidence: 44%
“…In 2015, NIST identified 3D geolocation as the top gap with highest priority for LBS R&D investment [231]. This highlights the importance of delivering vertical (i.e., height) location information, either in the form of absolute height value or floor label.…”
Section: Vertical Positioningmentioning
confidence: 99%
“…Further, the lack of indoor maps of public buildings creates a barrier to effective emergency operations. In 2015, a Location-Based Services (LBS) Summit to look at these and other problems was held with industry and academic members to determine what should be done first [4]. Improving means to share location was selected as a top priority.…”
Section: Problemmentioning
confidence: 99%
“…Converting from raster to vector format is technically complicated. 4 ESRI and QGIS have tools to do this, but the process may be time-consuming and the results can be inaccurate.…”
Section: Data Interoperability Problem In General Termsmentioning
confidence: 99%
See 1 more Smart Citation